Migração internacional e famílias domiciliares: arranjos, estratégias e conflitos em Governador Valadares, Minas Gerais - Nuni Vieira Jorgensen (2017)
The purpose of this research is to analyze the negotiations, arrangements and conflicts existing around international migration decision-making among emigrants and their family households, using as case study the city of Governador Valadares, Minas Gerais, Brazil. This has been done by using the theoretical frameworks developed by the New Economics of Labor Migration (NELM), and by the transnationalist theory, especially by the literature of transnational families. Methodologically, a mixed methods approach was carried out, using, on one hand, the collected data on international emigration of the 2010 Census and of the Survey on Migration, Vulnerability and Environmental Changes in the Rio Doce Valley; and, on the other hand, a content analysis of 20 in-depth interviews conducted in Governador Valadares, 2016. As results, it became clear that the flows towards the United States and Portugal have different sex and age selectivity, so that emigration from Governador Valadares needs to be regarded taking it account these specificities. In addition, the findings of this study show that households with international emigrants are significantly different from those without international emigrants, with the prevalence of single-parent and extended arrangements in the former. Moreover, the in-depth interviews demonstrated that these arrangements can be causes as well as consequences of the migratory processes. Finally, it was found that the decision making processes to migrate are highly complex and often do not involve a contract between emigrant and family households; frequently have non-economic motivations; and, generally, encompass various types of intrahousehold conflicts.